Towards creating the assessment methodology for urban road transport development projects - Griškevičiūtė-Gečienė, Aušrinė; Burinskienė, Marija (Technological and Economic Development of Economy, 2012)
The assessment of development on transport infrastructure is a very complicated process using different methods and complexity substantiating their necessity to the State and the society. Accomplished analysis of the assessment of development projects on transport infrastructure used in foreign countries and Lithuania shows that standardized and united methodology does not exist; however many methods and their modifications are used in transport sector. Moreover, there is a problem concerning the assessment of development projects of urban and rural road transport infrastructure in Lithuania. It is obvious that differences between urban and rural road transport infrastructure do exist, but Lithuanian practice shows that common methods are used during the process of preparation and evaluation of development projects, including common assessment aspects, criteria and result indicators.